Ultrafast opto-magnetism. (October 2015) - Kalashnikova, A M; Kimel, A V; Pisarev, R V
Abstract: In the last decade, a new area of research, referred to as femtomagnetism, has developed within the field of magnetism, which studies the excitation and control of magnetic medium dynamics on time scales comparable to or even much shorter than those of spin-lattice, spin-orbit, and exchange interactions. Among the many femtomagnetic processes studied to date, the opto-magnetic interaction of femtosecond laser pulses with media is of particular interest. This interaction is based on nondissipative Raman-type mechanisms and enables coherent spin dynamics to be efficiently and selectively excited and its parameters to be controlled. This review considers the key features of ultrafast opto-magnetic phenomena and how they relate to magneto-optical effects. A number of experimentally observed examples of ultrafast spin dynamics excited via opto-magnetic inverse Faraday and Cotton–Mouton effects are considered, and their microscopical nature is discussed. An experimental example is given demonstrating that combining ultrafast opto-magnetic phenomena with other laser-induced processes allows magnetization to be controlled on a picosecond time scale.